Drivers and obstacles to banking SMEs : the role of competition and the institutional framework - Torre, Augusto de la 1997- (Policy research working paper, 2008)
"This paper studies the factors banks perceive as drivers and obstacles to financing small and medium enterprises (SMEs), focusing on the role of competition and the institutional framework. Using a survey of banks in Argentina and Chile, the paper shows that, despite alleged differences in the countries' environments regarding rules, regulations, and ease of doing business, SMEs have become a strategic segment for most banks in both countries. In particular, banks have begun to target SMEs due to the significant competition in the corporate and retail sectors. They perceive the SMEs market as highly profitable, large, and with good prospects. Moreover, banks are developing coping mechanisms to overcome the particular institutional obstacles present in each country and to compete for SMEs. Banks' interest in SMEs is not based on government programs, yet policy action might help reduce the cost of providing financing, especially long-term lending. "--World Bank web site